Acute lower respiratory infections among children under five in Sub-Saharan Africa: a scoping review of prevalence and risk factors - Jacob Owusu Sarfo; Mustapha Amoadu; Thomas Boateng Gyan; Abdul-Ganiyu Osman; Peace Yaa Kordorwu; Abdul Karim Adams; Immanuel Asiedu; Edward Wilson Ansah; Forster Amponsah-Manu; Priscilla Ofosu-Appiah (BMC, 2023)
Abstract Background Acute lower respiratory tract infections (ALRTIs) among children under five are still the leading cause of mortality among this group of children in low and middle-income countries (LMICs), especially countries in sub-Saharan Africa (SSA). This scoping review aims to map evidence on prevalence and risk factors associated with ALRTIs among children under 5 years to inform interventions, policies and future studies. Methods A thorough search was conducted via four main databases (PubMed, JSTOR, Web of Science and Central). In all, 3,329 records were identified, and 107 full-text studies were considered for evaluation after vigorous screening and removing duplicates, of which 43 were included in this scoping review. Findings Findings indicate a high prevalence (between 1.9% to 60.2%) of ALRTIs among children under five in SSA. Poor education, poverty, malnutrition, exposure to second-hand smoke, poor ventilation, HIV, traditional cooking stoves, unclean fuel usage, poor sanitation facilities and unclean drinking water make children under five more vulnerable to ALRTIs in SSA. Also, health promotion strategies like health education have doubled the health-seeking behaviours of mothers of children under 5 years against ALRTIs. Conclusion ALRTIs among children under five still present a significant disease burden in SSA. Therefore, there is a need for intersectoral collaboration to reduce the burden of ALRTIs among children under five by strengthening poverty alleviation strategies, improving living conditions, optimising child nutrition, and ensuring that all children have access to clean water. There is also the need for high-quality studies where confounding variables in ALRTIs are controlled.